Mollusks from Southern Nichupté Lagoon, Quintana Roo, Mexico (Continued from Sterkiana No. 59) - Susan Fraker Carnes (Hello World!, 1975)
Representatives of 182 species of mollusks are present in sediments of southern Nichupte Lagoon, Quintana Roo Territory, Mexico. It is possible to recognize several molluscan assemblages in surface sediments. An Open Lagoon assemblage is recognized in subsurface sediments that were deposited during a time when Nichupte Lagoon was less restricted. (Cont.)